Perda de biodiversidade em função de pressão antrópica nas planícies inundáveis da Amazônia Maranhense - SILVA, Vilena Aparecida Ribeiro (2019)
The Floodplains of Maranhão or Baixada Maranhense, are an internationally strategic area for the biological conservation of wetlands of the Planet, being one of the Brazilian sites that are part of the Convention on Wetlands of International Importance known as the Ramsar Convention. This region also has anthropogenic pressures related to deforestation, burning and agricultural activity, which promote an intense reconfiguration of the landscape. The objective of this work is to evaluate the biodiversity loss caused by anthropic impacts in the floodplains of Maranhense Amazon. The study area is the municipality of Pinheiro, pole of the Baixada. For this purpose, remote sensing tools are used in particular: spatial and temporal analysis of outbreaks of wildfires and forest fires detected by “reference satellite” images, AQUA, MODIS sensor; shallow cut deforestation rate, estimated from the deforestation increments identified in the Landsat class satellite image covering the Legal Amazon; Normalized Difference Vegetation Index - NDVI, performed from the time series of the MOD13A3 product, processed in the ENVI application; land use and land cover analysis using MapBiomas Project data and the Linear Spectral Mixture Model; and calculating the EVI trend to analyze the condition of primary and secondary forests. This information will generate the database for an integrated ecosystem analysis that will lead to an understanding of the impacts of anthropogenic actions in the region, generating information that may assist in developing a balanced approach between conservation and sustainable use of natural resources.